USAGE OF VIRTUAL REALITY IN THE EDUCATIONAL PROCESS AND VOCATIONAL GUIDANCE ON THE EXAMPLE OF “VRANALYTICS” SOFTWARE - Vetchanin, Yevhen; Horbatovskyi, Dmytro (Educological discourse, 2020)
The present article delves into one of the most promising computer technologies in education - virtual reality. Current usage of virtual reality technology in education is quite low, though it has a large number of advantages compared to other modern information technologies and provides possibilities that other technologies do not have. You can find a small amount of articles that highlight usage of virtual reality technology in different fields of education and almost no articles about possibility of using virtual reality technology for vocational guidance in school. Therefore, the main objectives of this article are, first, to describe and analyze potential possibility of usage of virtual reality technology in the modern educational process and vocational guidance. Second, to consider a virtual reality software product “VRAnalytics” that is currently under development. The main three objectives of “VRAnalytics” are: 1. Serve as an information environment aimed at informing the user about the modern world of professions and different specialties that exist nowadays. 2. Create tasks for the user in the form of a set of different puzzles that he/she needs to solve in the virtual reality. The purpose of such tasks is to provide the user with knowledge of the specificities of various professions and information about his/her abilities and skills, as well as their level of development in these skills. 3. Analyze and storage received information for further usage in vocational guidance and counselling. In addition, in the article we compare VR technology with other modern computer technologies and describe advantages and disadvantages of using virtual reality technology in educational process and vocational guidance, such as visibility, security, interactivity, immersion and focusing.